INTEGRATING TELEMEDICINE INTO HEALTH INFORMATION TECHNOLOGY FOR IMPROVING HEALTHCARE QUALITY - Wulandari, Sri; Putri, Frestiany Regina (LPPM Universitas Duta Bangsa Surakarta, 2025)
The purpose of this study is to examine how the integration of telemedicine into Health Information Technology (HIT) contributes to the improvement of healthcare quality. The research specifically seeks to identify opportunities, benefits, and barriers associated with embedding telemedicine within digital infrastructures such as Electronic Health Records (EHRs), Health Information Exchange (HIE), and mobile health (mHealth) applications. To achieve this objective, a systematic literature review was carried out using the PRISMA 2020 framework. Relevant studies were retrieved from several open-access databases, including PubMed Central, BMJ Open, BMC Digital Health, JMIR, and the WHO Global Health Observatory. The search was limited to publications appearing between 2019 and 2025. Out of 150 records initially identified, 25 studies met the inclusion criteria after screening and full-text assessment. These studies comprised randomized controlled trials, case studies, reviews, and international health policy documents. The findings reveal five key contributions of telemedicine–HIT integration: improved interoperability, enhanced accessibility, increased operational efficiency, greater patient satisfaction, and better clinical outcomes in chronic disease management. Nevertheless, challenges such as uneven digital infrastructure, data protection concerns, and variable levels of digital literacy remain significant. The study concludes that national policies, adoption of global interoperability standards, and investment in digital health infrastructure are essential to ensure sustainable implementation.